Pengembangan Video Microlearning Edukasi Regulasi Diri (Disiplin Diri) pada Mahasiswa Atlet Karate Universitas Negeri Malang - Novi Febriyanti; Kurniati Rahayuni (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to develop microlearning educational videos on self-regulation (self-discipline) for karate student athletes at Malang State University. Self-regulation, especially in aspects of concentration and emotions, is very important for athletes to achieve optimal performance. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The analysis stage was carried out to identify the needs of karate student athletes regarding self-regulation. Based on the results of the analysis, microlearning material was designed and developed which includes concentration and emotional regulation techniques. This product was validated by karate coaching and sports psychology experts, and tested on small and large groups of karate athletes. The validation results show that the microlearning material has a high level of suitability, clarity, convenience and usefulness. Trials on athletes showed significant improvements in concentration and emotional regulation abilities after following this microlearning program. Athletes reported that the material was presented in an interesting and easy to understand manner, and could be applied effectively in training and competition. The conclusion of this research is that the development of microlearning educational videos on self-regulation (self-discipline) for karate student athletes at Malang State University is effective in improving athletes' concentration and emotional regulation abilities and is suitable as education for concentration and emotional regulation of karate student athletes at Malang State University. It is recommended that this program be integrated into the athlete's daily training curriculum and that periodic evaluations be carried out to ensure its effectiveness. Further development also needs to be carried out to update and add to the material so that it remains relevant to the latest developments in the field of sports psychology.